2017
DOI: 10.3389/fimmu.2017.01828
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Mitochondrial Reactive Oxygen Species and Cellular Redox Imbalance in Human NADPH-Oxidase-Deficient Phagocytes

Abstract: Chronic granulomatous disease (CGD) is caused by mutations in genes that encode the NADPH-oxidase and result in a failure of phagocytic cells to produce reactive oxygen species (ROS) via this enzyme system. Patients with CGD are highly susceptible to infections and often suffer from inflammatory disorders; the latter occurs in the absence of infection and correlates with the spontaneous production of inflammatory cytokines. This clinical feature suggests that NADPH-oxidase-derived ROS are not required for, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
3
37
0
1
Order By: Relevance
“…Cell pretreatment with H 2 O 2 is known to cause the excessive release of ROS, which initiates DNA and mitochondrial damage, resulting in cell apoptosis (Dai et al, 2014;Ding et al, 2016;Fu et al, 2016). Accumulating evidence has shown that ROS production is associated with oxidative stress and mitochondrial anomalies (Nesi et al, 2017;Sundqvist et al, 2017;Franco-Iborra et al, 2018). We found that a-cyperone reduced the production of ROS in H 2 O 2 -treated SH-SY5Y cells.…”
Section: A B C D Ementioning
confidence: 63%
“…Cell pretreatment with H 2 O 2 is known to cause the excessive release of ROS, which initiates DNA and mitochondrial damage, resulting in cell apoptosis (Dai et al, 2014;Ding et al, 2016;Fu et al, 2016). Accumulating evidence has shown that ROS production is associated with oxidative stress and mitochondrial anomalies (Nesi et al, 2017;Sundqvist et al, 2017;Franco-Iborra et al, 2018). We found that a-cyperone reduced the production of ROS in H 2 O 2 -treated SH-SY5Y cells.…”
Section: A B C D Ementioning
confidence: 63%
“…The results obtained from the studies of various cell types suggest that mitochondrial ROS can also affect antigen-dependent mast cell activation by modifying activities of MAPK and transcription factors NF-κB and NFAT. Stimulating the mitochondrial ROS production by antimycin A induces Erk1/2 phosphorylation and interleukin 8 (IL-8) secretion by polymorphonuclear leukocytes from human peripheral blood ( 78 ). There is evidence indicating that mitochondrial ROS are involved in activating P38 MAPK ( 79 , 80 ) and c-Jun N-terminal kinases (JNK) ( 81 ).…”
Section: The Role Played By Mitochondria In the Fcεri-dependent Mastmentioning
confidence: 99%
“…ROS are a by-product of the aerobic metabolism of organisms ( 21 ). It has previously been demonstrated that active oxygen is closely associated with tumor formation, cell cycle and apoptosis ( 22 ).…”
Section: Resultsmentioning
confidence: 99%